International workplace sexual harassment laws and developments for the multinational employer - Cobb, Ellen Pinkos, 1958- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"As the #MeToo movement has become an increasingly global and significant workplace matter, a timely resource compiling must know international workplace sexual harassment laws for the multinational employer is clearly needed. This book provides a comprehensive compilation of global sexual harassment laws, clearly necessary in this climate but not currently existing until now. It presents legislation addressing workplace sexual harassment in over 50 countries in the European Region, Asia Pacific, Americas, and the Middle East and Africa. Within each region, the laws of individual countries are set forth, as well as some cultural context and recent developments to indicate present and future trends in workplace sexual harassment regulation. Written in clear, plain English for anyone without a legal background to understand, this book is essential reading and a key resource for employment and business attorneys, global employers, managers, human resources professionals, and occupational health and safety professionals. Academics, practitioners, Union members, employees, NGOs, and those in the human rights field will also benefit from this timely resource"--
Workplace sexual harassment : the big picture, the role of culture, and the global view -- Sexual harassment in the European Union : dignity and directives -- Sexual harassment laws in European countries -- Sexual harassment laws in the Asia Pacific region -- Sexual harassment laws in the Americas region -- Sexual harassment laws in Middle East and African countries.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual harassment -- Law and legislation; Sex discrimination in employment -- Law and legislation; LAW / Business & Financial; LAW / Reference; BUSINESS & ECONOMICS / Business Law